The Influence of the Explicit Instruction Model on Learning Outcomes in Basketball Free Throw Shooting - Diah Novita Anggraini; Muchamad Arif Al Ardha; Advendi Kristiyandaru; Budi Prakoso (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
In the 2013 curriculum there are various learning materials that can be implemented by students as a means of physical activity, one of which is shooting free throw, in this material students have difficulty in understanding and lack of skill in implementation. The purpose of this study was to determine the effect of the explicit instruction model on shooting free throw learning outcomes. The type of research used is a pre-experiment with a one group pretest posttest design. The research sample was selected using cluster random sampling technique, consisting of 32 students of class VI-D SDN Rungkut Menanggal I/582 Surabaya. The research instrument used was a learning outcome test, which included a knowledge test in the form of 10 multiple choice questions, and a skill test in the form of 10x free throw shooting. Through the results of the Wilcoxon test and the results of the percentage increase, the knowledge showed a p-Value of 0.00 (sig <0.05) with an increase of 62.83%. Process-oriented skills show p-Value 0.00 (sig < 0.05) with an increase of 231%. Meanwhile, product-oriented skills showed a p-Value of 0.80 (sig ≥ 0.05). The results showed that the application of the explicit instruction model had an effect on the learning outcomes of free throw shooting in the aspects of knowledge and process-oriented skills, but had no effect on the aspects of product-oriented skills.